2008
DOI: 10.1186/1471-2334-8-68
|View full text |Cite
|
Sign up to set email alerts
|

Presence of qnr gene in Escherichia coli and Klebsiella pneumoniae resistant to ciprofloxacin isolated from pediatric patients in China

Abstract: BackgroundQuinolone resistance in Enterobacteriaceae results mainly from mutations in type II DNA topoisomerase genes and/or changes in the expression of outer membrane and efflux pumps. Several recent studies have indicated that plasmid-mediated resistance mechanisms also play a significant role in fluoroquinolone resistance, and its prevalence is increasing worldwide. In China, the presence of the qnr gene in the clinical isolates of Enterobacteriaceae has been reported, but this transmissible quinolone resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 23 publications
9
47
4
3
Order By: Relevance
“…In our samples, occurrence of bla genes was observed in the following order: bla TEM [ bla SHV [ bla CTX-M . Similar to our report QNR genes were less prevalent than bla genes among pathogenic bacteria in other countries [4,22,23]. Significant association between the presence of bla and QNR genes (as observed in the study) is of serious concern since quinolone resistant ESBL bacteria has limited treatment options.…”
Section: Discussionsupporting
confidence: 89%
“…In our samples, occurrence of bla genes was observed in the following order: bla TEM [ bla SHV [ bla CTX-M . Similar to our report QNR genes were less prevalent than bla genes among pathogenic bacteria in other countries [4,22,23]. Significant association between the presence of bla and QNR genes (as observed in the study) is of serious concern since quinolone resistant ESBL bacteria has limited treatment options.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, in other investigations carried out in China and the USA, it has been shown that qnrS (14.9%) and qnrA (14%) are the most prevalent of all K. pneumoniae clinical isolates screened by multiplex PCR, respectively [16,18]. The present investigation shows no qnrA in its clinical isolates; similarly, Minarini et al [13] and Saiful et al [19] in Brazil and Malaysia have indicated no qnrA or qnrS-positive isolates among their clinical isolates of K. pneumonia, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…Although the qnr gene indicates a low level of resistance to quinolones, its attendance aids the selection of chromosomal mutations, facilitating increased resistance in the host strain [9][10][11]. Frequency of qnr genes PMQR associated with the qnr genes in different human clinical enterobacterial isolates was determined first in the USA in 1994 using a K. pneumoniae isolate (later termed qnrA1) [9], which was then widely reported worldwide [12][13][14][15][16][17][18][19]. However, no study has been done on prevalence of qnr genes among enterobacterial clinical isolates in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Lin J-C, Chang F-Y, Fung C-P, Xu J-Z, Cheng H-P, Wang J-J, et al fluoroquinolones (15,16). The excessive use of antibiotics has further increased the incidence of antibiotic resistance in bacteria, resulting in treatment failure, development of complications, and increased cost of treatment (17). Because of the genetic variations in the bacterial strains and the difference in the frequency of antibiotic use, a drug resistance rate varies widely in different regions of the world.…”
Section: Conflict Of Interestmentioning
confidence: 99%